Pembuatan Video Testimoni Dalam Bahasa Jepang Sebagai Media Promosi Lembaga Pelatihan Kerja Rekadaya Karsa Utama (LPK REKATAMA) Sidoarjo - Mohammad Faizal Fuad Aziz; Izza Fauziyah (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2021)
The purpose of this study is to make testimonial videos in Japanese as a promotional medium for LPK Rekatama. These videos use two-language translations: Japanese-Indonesian and Indonesian-Japanese. This study used a qualitative descriptive method to describe the process of making the testimonial videos for LPK Rekatama. There were three stages in making these videos: pre-production, production, and post-production. The results of this study were in the form of testimonial videos in Japanese as a promotional medium for LPK Rekatama which lasted for 5 minutes and was published on social media, that was Instagram TV LPK Rekatama. The results of this study can be used as a reference for the production of advanced testimonial videos about other LPK Rekatama promotional media such as company profiles, banners, brochures, and other promotional media.